Analysis of slip systems in protein crystals with a triclinic form using a phenomenological macro-bond method. Issue 20 (10th May 2021) - Suzuki, Ryo; Shigemoto, Chika; Abe, Marina; Kojima, Kenichi; Tachibana, Masaru
Abstract : Slip systems in triclinic hen egg-white lysozyme (Tri-HEWL) crystals, which is one of typical protein crystals, were identified by the indentation method and the surface energy estimation using phenomenological macro-bond methods. Abstract : Slip systems in triclinic hen egg-white lysozyme (Tri-HEWL) crystals, which are typical protein crystals, were identified by an indentation method. Eleven kinds of slip systems are clearly observed. These slip systems are determined by surface energy estimation using phenomenological macro-bond methods. Based on the analysis of the slip systems, it can be suggested that the active slip systems are controlled by not the Burgers vector but the slip plane with lower surface energy for crystals with complex macromolecules and lower crystallographic symmetry such as Tri-HEWL crystals. This mechanism to decide active slip systems is unique compared with the conventional crystals such as FCC metals and covalent materials. It is expected to establish a more comprehensive dislocation theory including macromolecular crystals.